The Physicochemical and Sensory Qualities of Goat Cheese with Indigenous Probiotic Starter at Different Temperatures and Storage Durations - Setyawardani, Triana; Sulistyowati, Mardiati; Widayaka, Kusuma; Rahardjo, Agustinus Hantoro Djoko (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The research is conducted aiming at analyzing the physical, chemical, and sensory qualities of goat cheese with different temperatures and storage duration. The research materials are goat milk and L. plantarum TW14 and L rhamnosus TW2 isolates, and its equipments include a set of cheese production tools, colorimeter, and SEM. The variables analyzed are cheese’s physical quality (color and structure), chemical qualities (total titrated lactic acid) and sensory qualities (texture, flavor, aroma and likeness). The treatment consists of 2 factors, namely the first factor including: storage temperature (freezer and refrigerator) and the second factor: storage duration (0; 15; 30; 45 and 60 days) with 3 replicates. The obtained results indicate that storage temperature does not influence the cheese’s brightness level (L*), a* value (redness) and b* value (yellowness) and sensory qualities (texture, flavor, aroma and likeness), yet storage duration influences the cheese’s L* value (P<0.01). Storage temperature has significant influence (P<0.01) on the cheese’s lactic acid content, while storage duration has insignificant influence (P>0.05) on it. The cheese’s structure shows protein aggregate, void and lactic acid bacteria. The conclusion is that frozen-stored goat cheese still has good physical, chemical, and sensory qualities.